MODERN FORMS AND METHODS OF COMBATING CORRUPTION - Nalyvaiko, Larysa, Savchenko Valeria (SUPREMANCE OF LAW, 2019)
The article investigates modern forms and methods in the field of combating corruption in Ukraine. The main administrative legal approaches in the field of prevention and counteraction to corruption are proposed: electronic declaration, activity of the prosecutor’s office, creation of the Supreme Anti-corruption Court of Ukraine, etc. It is emphasised that electronic declaration is a means to improve the effectiveness of our state in the direction of eliminating corruption risks in the work of civil servants.
Keywords: democratic state; corruption; electronic declaration; prosecutor’s office; the Supreme Anticorruption Court of Ukraine